ANALISIS KERUSAKAN PERKERASAN LENTUR MENGGUNAKAN METODE PCI PADA JALAN RAYA MENGANTI, KOTA SURABAYA - Thoriqi Tri Rama Kusuma (Jurnal Teknik Sipil Info Manpro, 2023)
Jalan Menganti Surabaya is a City Road which is managed directly by the Surabaya City Government, however, it faces the same problems and difficulties in maintaining its quality as other roads in Indonesia, damage to the road surface is one of the problems that often occurs on this road. This research was carried out on Jalan Raya Menganti Wiyung - Babatan with a total road length of 4 km with a 4/2D road type and flexible pavement. This research is very important because Jalan Raya Menganti directly connects Surabaya City with Gersik Regency, therefore this road is very vital and experienced quite significant damage, both light damage, moderate damage and heavy damage to this road section. Jalan Raya Menganti is a Collector Road and Class III Road managed by the Surabaya City Government. The aim of this research is to identify and analyze types of road damage using the PCI method and analyze the appropriate type of repair. The process of repairing and maintaining road hardness will be completed using the PCI (Pavement Condition Index) method. This survey uses simple tools and divides the road into 40 segments, each segment measuring 7 x 200 meters. The results of this research are that the condition of Jalan Raya Menganti Wiyung – Babatan is very good with a PCI value of 81.606. So the conclusion of this research is that it can propose an appropriate repair technique for Jalan Raya Menganti Wiyung - Babatan Surabaya, namely the addition of new pavement (Overlay).